Patient‐Derived Melanoma Immune‐Tumoroids as a Platform for Precise High throughput Drug Screening - Juliana Viegas; Sofia Costa; Sofia Dias; Catarina Leite Pereira; Bruno Sarmento (Advanced Science)
Abstract In vitro models are crucial in cancer research, but they must truthfully mimic in vivo tumors for clinical relevance. The development of unprecedent melanoma quadruple multicellular tumoroids (MCTs) is proposed comprising tumor cells, keratinocytes, fibroblasts, and monocytes that replicate tumor architecture, tumor microenvironment, and secretome behavior. These MCTs of 300 µm in diameter secreted keratin and collagen, showing complexity proportional to their cell combinations. Further, closely resembled in vivo tumors in terms of cells organization, growth, progression, and immune behavior. Drug screening using these MCTs demonstrated their potential as patient‐derived platforms for precision medicine. These findings highlight the true value of MCTs for studying melanoma biology and testing therapeutic interventions with greater precision and relevance to human disease.